Sweet justice [compact disc] - Maidza, Tkay, 1996- (4AD, 2023)
Bright, soulful, and seductive, the second album by Los Angeles-based, Zimbabwe-born, Australia-raised Tkay Maidza shows off every facet of the irrepressible Tkay: her lacerating wit and infectiousness, her staunch self-belief and refusal to compromise. The result of a dark night of the soul, and ensuing epiphany, which led to a series of professional and personal reckonings, this isn't a revenge album, but it does stem from a profound sense of karma. Tkay has never sounded more liberated, or like she's having more fun. She flits effortlessly between styles, letting her irrefutable personality be the connective tissue. The album is an album that embodies the beautiful contradictions of Tkay's art: it's a coming-of-age record by someone who's mastered the game; an album about karmic justice and accountability that's bright, breezy, and incredibly fun, eviscerating those who are dishonest and disrespectful with a venom-laced kiss.